Biodiversité marine et exploitation biotechnologique des océans - Yves Le Gal (VertigO)
The large marine biodiversity is the consequence, on one hand of a very long evolutionary history which allowed the primitive living organisms to experiment very numerous molecular models and exploit a large panel of adaptations to very different environments, but also of the three-dimensional structure of the multiple marine ecosystems. To that, one has to add the multiplicative effect created by the cross-interactions between infinity of ecosystems of any sizes. This biological diversity is, in its global nature, very different from that observed on the continental space: as shown by the presence, in the oceans, of numerous endemic phylums but also as suggested by the recent discovery of many “new” marine living organisms of any sizes and of new forms of organization of living systems. This has practical consequences. The marine biomasses and their variety constitute a set of exploitable and up-gradable resources, many of them being potentially useful for man. The sectors of food industry are concerned as those of healthcare. An extraordinary field of biotechnological applications is now being opened.